PENGGUNAAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR IPS MATERI LETAK DAN LUAS INDONESIA - CHIKMAH CHIKMAH (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to improve student learning outcomes on the material location and area of ??Indonesia by using a problem based learning model. The research used is classroom action research. With the researched application of the use of problem based learning learning model in increasing student activity and learning outcomes. The results showed that there was an increase in student learning outcomes from pre-cycle, cycle I to cycle II, namely in the pre-cycle it was known that the knowledge competency learning outcomes from the number of students were 32, there were only 7 (21.88%) students who scored >73 (KKM) with a score of class average 55.88; in the first cycle there was an increase to 21 (65.63%) students who achieved the KKM with an average grade of 74.84 and in the second cycle there were 29 (90.63%) students who scored reaching the KKM with a grade class average 82.38. This increase in learning outcomes is also found in skills or performance learning outcomes where in the pre-cycle there were only 9 (28.13%) students who achieved the KKM (73) with a class average of 59.06; in the first cycle there were 19 (59.37%) students who scored reaching the KKM with an average grade of 75.59 and the second cycle had reached 32 (100%) students who scored reaching the KKM with a class average 80.06. The increase in student learning outcomes also appears in the attitude competence, although all students have reached the KKM since the pre-cycle, the increase in the sikpa score, namely in the pre-cycle who got the attitude A score was 3 (9.38%), students who got the attitude B score were 29 (90.63%), in the first cycle there were 13 (40.63%) students who got category A or very good and there were 19 (59.37%) students who got category B or good, in the second cycle there were 18 (56.25%) students got category A or very good and there were 14 (43.75%) students who got category B or good and no students got C (enough) or D (less). ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar siswa pada materi letak dan luas Indonesia dengan menggunakan model problem based learning. Penelitian yang digunakan adalah penelitian tindakan kelas. Dengan yang diteliti penerapan penggunakan model pembelajaran problem based learning dalam peningkatan keaktifan dan hasil belajar siswa. Hasil penelitian menunjukkan adanya peningkatan hasil belajar siswa dari pra siklus, siklus I hingga siklus II yaitu pada pra siklus diketahui hasil belajar kompetensi pengetahuan dari jumlah siswa 32 hanya ada 7 (21,88%) siswa yang mendapatkan nilai >73 (KKM) dengan nilai rata-rata kelas 55,88; pada siklus I sudah ada peningkatan menjadi 21 (65,63%) peserta didik yang mencapai KKM dengan nilai rata-rata kelas 74,84 dan pada siklus II sudah ada 29 (90,63%) peserta didik yang mendapatkan nilai mencapai KKM dengan nilai rata-rata kelas 82,38. Peningkatan hasil belajar ini juga terdapat pada hasil belajar keterampilan atau kinerja dimana pada pra siklus hanya ada 9 (28,13%) siswa yang mencapai KKM (73) dengan nilai rata-rata kelas 59,06; pada siklus I sudah ada 19 (59,37%) peserta didik yang mendapatkan nilai mencapai KKM dengan nilai rata-rata kelas 75,59 dan siklus II sudah mencapai 32 (100%) peserta didik yang mendapatkan nilai mencapai KKM dengan rata-rata kelas 80,06. Peningkatan hasil belajar siswa juga tampak pada kompetensi sikap, walaupun seleuruh siswa sudah mencapai KKM sejak pra siklus, peningkatan pada nilai sikpa yaitu pada pra siklus yang mendapatkan nilai sikap A ada 3 (9,38%), siswa yang mendapatkan nilai sikap B ada 29 (90,63%), pada siklus I menjadi 13 (40,63%) peserta didik yang mendapatkan kategori A atau amat baik dan ada 19 (59,37%) peserta didik yang mendapatkan kategori B atau Baik, pada siklus II ada 18 (56,25%) peserta didik yang mendapatkan kategori A atau amat baik dan ada 14 (43,75%) peserta didik yang mendapatkan kategori B atau Baik dan tidak ada siswa yang mendapatkan nilai C (cukup) ataupun D (kurang).